(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Polycystic Ovarian Syndrome (PCOS) is a complex endocrine and metabolic disorder, typically characterized by anovulation, menstrual irregularities, obesity, infertility, insulin resistance and polycystic ovaries. Conventional management relies on hormonal therapy, insulin sensitizers, ovulation-inducing agents and surgical options include laparoscopic ovarian drilling and cyst aspiration. From an Ayurvedic perspective, PCOS is understood as Kapha-Medo dushti with vitiation of Vata and Pitta, resulting in Agnimandya, Formation of Ama, and Srotorodha in Artavavaha Srotas, leading to impaired folliculogenesis. A 26-year-old female with chronic anovulatory cycles was treated using a comprehensive Ayurvedic protocol involving Shodhana, Samana and Rasayana chikitsa. The treatment aimed at restoring metabolic balance, clearing Srotorodha and normalizing ovarian function. Post-treatment follicular monitoring demonstrated ovulation, signifying restoration of physiological Ritu Chakra. This case underscores the potential of Ayurvedic management in re-establishing ovulatory function and menstrual regularity in PCOS without the complications of hormonal therapy.